Addition of Vitamin C on Diet to Improve Immunity on Tiger Grouper, Epinephelus fuscoguttatus to Infection Viral Nervous Necrosis - Johnny, F.; Mahardika, K.; Giri, I.N.A.; Roza, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
An attempt with a purpose to improve the fish seed immunity tiger grouper, Epinephelus fuscoguttatus to infection viral nervous necrosis (VNN) with addition of vitamin C have been done in Gondol Research Institute for Mariculture, Bali. Fish seed tiger grouper counted 400 fishes with wight between 35-55 disperse gram into 4 polycarbonate tanks volume of 1000 litres with density of 100 fish/tank. Each tank is equipped with flow-through water system and aeration. Experimental diets were formulated to have the same nutrients content except of vitamin C stable form (L-ascorbyl-2-Phosphate-Magnesium) with different dose, that is 0; 300; 600; 1.200 mg/kg diet was added to each formula. Experimental diets were prepared as dry pellet using freeze dryer Fish fed experimental diets twice everyday during 60 day. After 20, 40, and 60 days after treatment test to challange with VNN. Perception of test fish immunities parameter done to phagocytic activity (PA), make of phagocytic index (PI) and lysozyme activity (LA). Attempt result indicated that addition of vitamin C in diet dose between 600-1,200 mg/kg after 60 treatment day yield highest survival rate, PA and LA compared to other treatments. Keywords: Immunity, tiger grouper, viral nervous necrosis, vitamin C ABSTRAK Suatu percobaan dengan tujuan meningkatkan imunitas benih ikan kerapu macan, Epinephelus fuscoguttatus terhadap infeksi viral nervous necrosis (VNN) dengan penambahan vitamin C telah dilakukan di Balai Besar Riset Perikanan Budidaya Laut Gondol, Bali. Benih ikan kerapu macan sebanyak 400 ekor dengan bobot antara 35-55 gram ditebar ke dalam 4 buah bak polikarbonat volume 1000 liter dengan kepadatan 100 ekor/bak, menggunakan sistem air laut mengalir dan diaerasi. Ikan diberi pakan percobaan 2 kali sehari dan dipelihara selama 60 hari. Formulasi pakan percobaan diatur mempunyai kandungan nutrien yang sama kecuali kandungan vitamin C. Pada formula pakan ditambahkan vitamin C bentuk stabil (L-ascorbyl-2-Phosphate-Magnesium) dengan dosis berbeda, yaitu 0; 300; 600; 1.200 mg/kg pakan. Pakan dibuat dalam bentuk pelet dan dikeringkan menggunakan